Usage of electronics and generation of E-waste in Singapore - Aw, Li Ling (2023)
The global consumer electronics market has grown at 4.50% annually and forecasted to break US$1 trillion by 2029, with expected 3 billion users out of a global population of 8 billion. As consumer electronics become an indispensable part of our everyday lives, electronic waste (E-waste) has become a critical global concern as E-waste correspondingly is expected to increase by 30% by 2030. E-waste, if not properly dealt with, are hazards to population health and damaging to the environment, not to say that high economic values worth at least US$60 billion are lost through improper reuse of precious metals. Only 17% of E-waste are currently recycled.